2022
DOI: 10.29244/jcfcs.1.3.229-238
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Food Waste Campaign Content on the Hashtag #Habiskanmakananmu on Instagram

Abstract: The rise of food waste issues has prompted the implementation of several social campaigns, one of which is the #HabiskanMakananmu social campaign. This study aims to identify the characteristics and analyze the effectiveness of social campaign content on #HabiskanMakananmu on Instagram. This research is an exploratory design with a content analysis method. The data collection used a purposive sampling technique of 200 social campaign content on Instagram using the content analysis method. The data was processe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 12 publications
(12 reference statements)
0
10
0
Order By: Relevance
“…It has been demonstrated that the use of graphics, titles, and standard language while delivering communications ensures that everyone can comprehend and properly analyze the messages conveyed. Campaigns and seminars play a vital role in not only raising awareness but also helping people improve their behavior and become more sympathetic to the problem of food waste [41]. The target audience of community education is divided into three groups, adults, youth, and children.…”
Section: Figure 2 the Article Type Of Food Waste Communitymentioning
confidence: 99%
“…It has been demonstrated that the use of graphics, titles, and standard language while delivering communications ensures that everyone can comprehend and properly analyze the messages conveyed. Campaigns and seminars play a vital role in not only raising awareness but also helping people improve their behavior and become more sympathetic to the problem of food waste [41]. The target audience of community education is divided into three groups, adults, youth, and children.…”
Section: Figure 2 the Article Type Of Food Waste Communitymentioning
confidence: 99%
“…One of them is displaying numbers or percentages of Indonesia's food waste which can increase audience awareness about food waste since they are aware of how this issue is to their daily life. The third research has a similar deficiency to the first research which is social media consideration to reach more audience and there is no further explanation in the evaluation result [7]. The gap in the last research is mainly because the solution given in the content is not varied enough since it is more focus on warning and advisory information [7].…”
mentioning
confidence: 97%
“…The third research has a similar deficiency to the first research which is social media consideration to reach more audience and there is no further explanation in the evaluation result [7]. The gap in the last research is mainly because the solution given in the content is not varied enough since it is more focus on warning and advisory information [7].…”
mentioning
confidence: 97%
See 2 more Smart Citations